India's ancient past - Sharma, Ram Sharan. 1920-2011. (Delhi ; Oxford : Oxford University Press, 2005)
This volume presents a comprehensive yet accessible account of ancient Indian history covering a wide spectrum, from the Neolithic and Chalcolithic cultures and the Harappan civilizations to the Guptas and Harshavardhana.
Originally published: 2005.
Includes bibliographical references and index.
Description based on print version record.
Keywords: India -- History -- To 324 B.C.; India -- History -- 324 B.C.-1000 A.D.